2020
DOI: 10.25259/sni_152_2020
|View full text |Cite
|
Sign up to set email alerts
|

Laser interstitial thermal therapy as an adjunct therapy in brain tumors: A meta-analysis and comparison with stereotactic radiotherapy

Abstract: Background: Minimally invasive procedures are gaining widespread acceptance in difficult-to-access brain tumor treatment. Stereotactic radiosurgery (SRS) is the preferred choice, however, laser interstitial thermal therapy (LITT) has emerged as a tumor cytoreduction technique. The present meta-analysis compared current SRS therapy with LITT in brain tumors. Methods: A search was performed in Lilacs, PubMed, and Cochrane database. Patient’s demographics, tumor location, therapy used, Karnofsky performance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…These limitations have been reported in multiple studies, emphasizing the critical need for more extensive, well-designed studies incorporating control groups to provide more conclusive insights into the intricate relationship between LITT and wound complications in brain tumour patients. [32][33][34][35] F I G U R E 4 Subsequent binary outcome meta-analysis of wound incidences. (A) Forest Plot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations have been reported in multiple studies, emphasizing the critical need for more extensive, well-designed studies incorporating control groups to provide more conclusive insights into the intricate relationship between LITT and wound complications in brain tumour patients. [32][33][34][35] F I G U R E 4 Subsequent binary outcome meta-analysis of wound incidences. (A) Forest Plot.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the comparatively smaller sample sizes and varied patient demographics in different studies could have impacted the observed heterogeneity and effect sizes. These limitations have been reported in multiple studies, emphasizing the critical need for more extensive, well‐designed studies incorporating control groups to provide more conclusive insights into the intricate relationship between LITT and wound complications in brain tumour patients 32–35 …”
Section: Discussionmentioning
confidence: 99%
“…In the form of image-guided surgery (IGS), stereotactic surgery uses several imaging modalities, including CT and MRI, to produce a precise map of the brain [142] [143]. The surgeon then used this map to precisely direct a surgical tool, such as a drill or biopsy needle, to the tumor's position.…”
Section: A) Stereotactic Surgerymentioning
confidence: 99%